Sporadic miscarriage: evidence to provide effective care. Issue 10285 (1st May 2021) - Coomarasamy, Arri; Gallos, Ioannis D; Papadopoulou, Argyro; Dhillon-Smith, Rima K; Al-Memar, Maya; Brewin, Jane; Christiansen, Ole B; Stephenson, Mary D; Oladapo, Olufemi T; Wijeyaratne, Chandrika N; Small, Rachel; Bennett, Phillip R; et al.
Summary: The physical and psychological effect of miscarriage is commonly underappreciated. The journey from diagnosis of miscarriage, through clinical management, to supportive aftercare can be challenging for women, their partners, and caregivers. Diagnostic challenges can lead to delayed or ineffective care and increased anxiety. Inaccurate diagnosis of a miscarriage can result in the unintended termination of a wanted pregnancy. Uncertainty about the therapeutic effects of interventions can lead to suboptimal care, with variations across facilities and countries. For this Series paper, we have developed recommendations for practice from a literature review, appraisal of guidelines, and expert group discussions. The recommendations are grouped into three categories: (1) diagnosis of miscarriage, (2) prevention of miscarriage in women with early pregnancy bleeding, and (3) management of miscarriage. We recommend that every country reports annual aggregate miscarriage data, similarly to the reporting of stillbirth. Early pregnancy services need to focus on providing an effective ultrasound service, as it is central to the diagnosis of miscarriage, and be able to provide expectant management of miscarriage, medical management with mifepristone and misoprostol, and surgical management with manual vacuum aspiration. Women with the dual risk factors of early pregnancy bleeding and a history of previous miscarriage can be recommended vaginal micronised progesterone to improve the prospects of livebirth. We urge health-care funders and providers to invest in early pregnancy care, with specific focus on training for clinical nurse specialists and doctors to provide comprehensive miscarriage care within the setting of dedicated early pregnancy units.